Turbinatine, a potential key intermediate in the biosynthesis of corynanthean-type indole alkaloids - Cardoso, C. L.; Silva, DHS; Tomazela, D. M.; Verli, H.; Young, MCM; Furlan, Maysa [UNESP]; Eberlin, M. N.; Bolzani, Vanderlan da Silva [UNESP] (Amer Chemical Soc, 2003)
Extraction of the leaves of Chimarrhis turbinata has led to the isolation of turbinatine (1), a new corynanthean-type indole alkaloid, besides four known indole alkaloids, strictosidine, 5alpha-carboxystrictosidine, vallesiachotamine, and isovallesiachotamine. The structural determination of 1 was based on 1D and 2D spectroscopic data. An evaluation of the DNA-damaging activities of the isolates was performed by means of a bioassay using mutant strains of Saccharomyces cerevisiae, which indicated these compounds were weakly active.